Characterisation of Hanseniaspora Isolates with Potential Aroma-enhancing Properties in Muscat Wines - López, S.; Mateo, J.J.; Maicas, S. Maicas (South African Journal of Enology and Viticulture, 2016)
The sensorial characteristics of the wines produced with Muscat grapes are related to the level of terpene alcohols, so an improvement of such a level is expected as a result of hydrolytic processes conducted by Hanseniaspora. The aim of this work was to select and identify new strains for this purpose. In a second step, the strains were assayed to evaluate their oenological abilities. H. uvarum H107 and H. vineae G26 and P38 were proven to be good candidates to be used in commercial vinification processes to enhance wine properties. Wine inoculated with yeasts showed an increase in the level of aromatic compounds.